A Review of SiC Sensor Applications in High-Temperature and Radiation Extreme Environments - Quanwei Zhang; Yan Liu; Huafeng Li; Jue Wang; Yuan Wang; Fabin Cheng; Haijun Han; Peng Zhang (Sensors)
Sensors operating in extreme environments are currently a focal point of global research. Extreme environmental conditions, such as overload, vibration, corrosion, high pressure, high temperature, and radiation, can affect the performance of sensors to the point of failure. It is noteworthy that, compared to the resistance to overload and vibration achieved through structural design, the application of sensors under high-temperature and radiation extreme conditions poses a greater challenge. Silicon carbide (SiC) material, due to its excellent physical and chemical properties, such as a large band gap and high atomic critical displacement energy, demonstrates outstanding potential for application in high-temperature and radiation extreme environments. This review presents the current status and research progress of SiC sensors in high-temperature and radiation extreme environments. Finally, given the limited research on the radiation resistance of SiC sensors, it identifies several challenges and research deficiencies in the application of SiC sensors under radiation extreme environments and discusses the future development direction of SiC-based substrate sensors.